Mental health, coping skills and academic performance in undergraduate students - Cuamba Osorio, Nehemías (Consorcio de Universidades Mexicanas A.C., 2020)
The university environment is a context that presents challenges to the student and increases the likelihood of mental health problems if they do not possess the skills required to face them, a phenomenon that affects different spheres. Aiming to identify the presence of mental health problems indicators and coping skills in undergraduate students, and to analyze the differences between the variables related to mental health problems and coping skills between groups of academic performance in undergraduate students, a quantitative cross-sectional research was structured. A sample of 688 answered two instruments, one to evaluate mental health and another one to assess coping skills. Results were analyzed globally and by career, and differences in academic performance were searched. Results showed that more than half of the students presents indicators of mental health problems, as well as problems in the execution of coping skills. There were no differences in the comparative analysis, results are discussed.